Supervise dan Pengawasan dalam Pendidikan - Arini Yahdillah; Wahidmurni; Indah Aminatuz Zuhriyah (EduInovasi: Journal of Basic Educational Studies, 2024)
In the field of education and teaching, supervisors are needed who can dialogue and help personal and professional growth so that everyone experiences personal and professional improvement. The principal has the obligation to regulate the running of the school and can also work closely with the community, raise the enthusiasm of the teacher staff and school employees to work better, build and maintain a family, cohesiveness and unity between teachers, employees and students. students, develop school curricula, know school plans and know how to implement them, pay attention to and seek the welfare of teachers and employees. Supervision can be carried out by the principal who acts as a supervisor, although in a modern educational organizational system, special supervisors are needed who are more independent, and can increase objectivity in coaching and carrying out their duties. The function of supervision or supervision in education is not just a control to see whether all activities have been carried out in accordance with the plans and programs that have been outlined, but more than that. Supervision in education contains a broader meaning. Supervision activities include determining the conditions or requirements of personnel and materials needed for the creation of an effective teaching and learning situation, and efforts to fulfill these requirements.